Anesthetic Zombanol: The Horror Effect in the Fabrication of Evil as a Representation of the Other in Movies Based on a True Story - Alves, Werner Almeida (Cadernos do IL, 2024)
This article approaches the claim of truth in the representation of zombies and elements of the Haitian folklore recreated in the American imaginary as a way to reinforce the evil Other through the fictionalization of historical accounts in movies under the umbrella label “Based on a True Story”. The movies in question are White Zombie (1932) and The Serpent and the Rainbow (1988) which claim to be based on factual accounts reported in the non-fiction books respectively The Magic Island, by Seabrook, and The Serpent and the Rainbow, by Davis, as a technique to amplify the horror effect in their viewers, and thus, resulting in the reinforcement of that very representation of the evil Other in the mainstream culture.